The National Violent Death Reporting System: an exciting new tool for public health surveillance. (14th December 2006) - Steenkamp, M; Frazier, L; Lipskiy, N; DeBerry, M; Thomas, S; Barker, L; Karch, D
Abstract : The US does not have a unified system for surveillance of violent deaths. This report describes the National Violent Death Reporting System (NVDRS), a system for collecting data on all violent deaths (homicides, suicides, accidental firearms deaths, deaths of undetermined intent, and deaths from legal intervention, excluding legal executions) in participating states. The NVDRS centralizes data from many sources, providing a more comprehensive picture of violent deaths than would otherwise be available. The NVDRS collects data on victims, suspects, and circumstances related to the violent deaths. Currently, 17 US states participate in the NVDRS; the intention is for the NVDRS to become a truly national system, representing all 50 states, the District of Columbia, and the US territories. This report describes the history of the NVDRS, provides an overview of how the NVDRS functions, and describes future directions.